2016
DOI: 10.5194/bg-2016-318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrothermal activity lowers trophic diversity in Antarctic sedimented hydrothermal vents

Abstract: 17 18Sedimented hydrothermal vents are those in which hydrothermal fluid vents through sediment 19 and are among the least studied deep-sea ecosystems. We present a combination of microbial 20 and biochemical data to assess trophodynamics between and within hydrothermally active and 21 off-vent areas of the Bransfield Strait (1050 -1647m depth). Microbial composition, biomass 22 and fatty acid signatures varied widely between and within vent and non-vent sites and 23 provided evidence of diverse metabolic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…0.28, figure 3 ) and an unidentified species of echiuran (mean 10.28‰ ± s.d. 0.01, figure 3 ), consistent with observations of a morphologically similar species of echiuran at a sediment-hosted hydrothermal vent in the Bransfield Strait [ 49 ]. This may indicate selective feeding strategies that favour OM that had been recycled by microbial activity, resulting in a relatively high trophic level.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…0.28, figure 3 ) and an unidentified species of echiuran (mean 10.28‰ ± s.d. 0.01, figure 3 ), consistent with observations of a morphologically similar species of echiuran at a sediment-hosted hydrothermal vent in the Bransfield Strait [ 49 ]. This may indicate selective feeding strategies that favour OM that had been recycled by microbial activity, resulting in a relatively high trophic level.…”
Section: Discussionsupporting
confidence: 88%
“…The vast majority of the species that occurred in sufficient abundance for SIA were annelid taxa with no carbonate structures. A pilot study confirmed that acidification had little impact upon δ 13 C measurements, and it was considered more appropriate to preserve the integrity of nitrogen and sulfur isotope signatures [ 48 , 49 ] at the expense of a small increase in error for carbon isotope measurements. There are usually substantial differences in signatures of methanotrophic and photosynthetic C-fixation pathways, making mixed diets clearly detectable even with an additional δ 13 C error.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to thermal decomposition of sediments, SHVs may contain high concentrations of chemosynthetic substrates, particularly methane 9 , 15 , 16 . Chemosynthetic production occurs through several pathways, such as sulphide or hydrogen oxidation or anaerobic oxidation of methane and there is now also evidence of diverse microbial lineages associated with other pathways, such as iron oxidation 17 20 . Fauna living in these habitats have access to both chemosynthetic and photosynthetic energy sources, while their distribution and behaviour reflect a balance between their ability to tolerate the high temperature, reducing conditions introduced by the influx of hydrothermal fluid and selectivity of the relative amounts of organic matter present 4 , 13 .…”
Section: Sedimented Hydrothermal Ventsmentioning
confidence: 99%
“…Fauna living in these habitats have access to both chemosynthetic and photosynthetic energy sources, while their distribution and behaviour reflect a balance between their ability to tolerate the high temperature, reducing conditions introduced by the influx of hydrothermal fluid and selectivity of the relative amounts of organic matter present 4 , 13 . The environmental gradients between SHVs and background sediments therefore create a range of assemblage compositions, trophic structures and pathways for in situ productivity 4 , 6 , 13 , 17 , 21 , 22 . We report here, for the first time in a sedimented vent system, how this affects energy transfers within food webs and the extent to which chemosynthetic production subsidises the diet of non-specialist fauna.…”
Section: Sedimented Hydrothermal Ventsmentioning
confidence: 99%